Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3390/w7030836
|View full text |Cite
|
Sign up to set email alerts
|

Soil and Waste Matrix Affects Spatial Heterogeneity of Bacteria Filtration during Unsaturated Flow

Abstract: Discontinuous flows resulting from discrete natural rain events induce temporal and spatial variability in the transport of bacteria from organic waste through soils in which the degree of saturation varies. Transport and continuity of associated pathways are dependent on structure and stability of the soil under conditions of variable moisture and ionic strength of the soil solution. Lysimeters containing undisturbed monoliths of clay, clay loam or sandy loam soils were used to investigate transport and pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A large body of information has been reported in previous studies about bacteria transport and physical, chemical, and biological soil properties, and manure types (e.g., Bradford et al, 2013;Engstr€ om et al, 2015;Unc et al, 2012Unc et al, , 2015. However, as mentioned earlier, this knowledge gap has still remained unexplored on how physics of solid manures impacts bacteria fate (Blaustein et al, 2015;Stocker et al, 2020a).…”
Section: Evaluation Of the Manure-treated Soil Btcsmentioning
confidence: 99%
“…A large body of information has been reported in previous studies about bacteria transport and physical, chemical, and biological soil properties, and manure types (e.g., Bradford et al, 2013;Engstr€ om et al, 2015;Unc et al, 2012Unc et al, , 2015. However, as mentioned earlier, this knowledge gap has still remained unexplored on how physics of solid manures impacts bacteria fate (Blaustein et al, 2015;Stocker et al, 2020a).…”
Section: Evaluation Of the Manure-treated Soil Btcsmentioning
confidence: 99%
“…The retention of E. coli in root zone could be attributed to six reasons, namely: First, the retention was because of the filtration of E. coli in the soil and adsorption of E. coli cells to soil particles (Ling et al 2009); secondly, the size of bacteria ranged from 0.2 to 5 lm compared to the fine to medium pore size of 10 nm to 10 lm, mechanical filtration of bacteria could occur, though it would be incomplete (Matthess et al 1988); thirdly, adsorption occurs between E. coli and soil particles and two strains of E. coli have shown that cells adhered rapidly to clay particles and formed cell-clay complexes, which adhere to each other or to other clay particles and form cell-clay aggregates at a much lower rate (Hattori 1970); fourth, E. coli established equilibrium in the soil water system, and the percentage of E. coli adsorbed depended on the clay and clay loam soil content in the VFSs; fifth there is equilibrium of E. coli in the soil water system in clay soil (Ling et al 2002b); and sixth, the E. coli die-off, sedimentation, adsorption and filtration with biofilms attachment on soil macropores will enhance the decline of bacteria during the transport of active vegetative microbial organisms, in VFSs (Unc et al 2015). This study had some limitations despites.…”
Section: 4mentioning
confidence: 99%
“…Little data exist on the transport mechanisms in overland flow pathways (Kasaraneni et al 2014). In soil, E. coli could be recovered during its travel time into soil matrix by die-off, sedimentation, adsorption and filtration (Unc et al 2015). E. coli transport mechanisms could be linked to organic carbon levels on those soils.…”
Section: Introductionmentioning
confidence: 99%